Tritrophic interactions among plants, herbivores and plant mutualists - Koski, Tuuli-Marjaana (fi=Turun yliopisto|en=University of Turku|, 2017)
Plants form the first trophic level in terrestrial ecosystems and provide energy and nutrients to higher trophic levels. Herbivores, frugivores or fungal endophytes use plants directly, while predators consume plants indirectly by consuming herbivores. However, species are often simultaneously interacting with antagonistic and mutualistic partners at various trophic levels. For this reason, the outcomes of species interactions can indirectly affect other species in the community. The aim of my thesis was to study tritrophic interactions between plants, their antagonists, such as insect or avian herbivores, and mutualists such as insectivorous or frugivorous birds and symbiotic endophyte fungus. In Chapters I-III I concentrated on the interactions among plants, herbivores and protective plant mutualists. In the first two Chapters, I investigated whether birds use volatile organic compounds or changes in visual properties of leaves from herbivore-damaged trees as foraging cues. I found that trees respond to herbivore damage both locally and systemically, but the olfactory foraging cue hypothesis was not supported. Instead, herbivory affected visual properties of leaves viewed by birds, although these changes may be in the limit of detection to them. In addition, my results indicate that cryptically coloured herbivores may have slightly better camouflage when on herbivore-damaged trees, although the herbivores are discriminable to birds against the leaves of the host plant regardless of the treatment (Chapter II). In Chapter III I studied the relationship between plants and protective fungal symbiont by testing whether systemic endophyte fungi can protect grasses against wild avian grazers. In this study I used two grass species, red fescues and tall fescues, which differ in texture. Both species have naturally both endophytic and non-endophytic individuals. I found that softer red fescue was preferred over coarse tall fescue, regardless of the endophyte status. In Chapter IV I studied the interaction between plants, herbivores and seed-dispersing mutualists. I tested whether insect herbivory causes allocation cost to fleshy fruiting plants by affecting ripening or chemical composition of berries. I also investigated potential ecological cost of herbivory measured as probability for ripe berries to be removed by frugivorous birds. I found that berries in undamaged ramets neighbouring herbivore-damaged conspecifics had lower probability to be removed by frugivores, although herbivory did not affect ripening or chemical composition of berries. This indicates that in clonal plants, herbivore damage may cause priming effect on neighbouring ramets, which can affect plant mutualists. The results of this thesis extend current knowledge about plant responses to herbivory, and also how these responses affect plant mutualists. In addition, my thesis provides information about the foraging behaviour of herbivores and plant mutualists. This kind of knowledge is essential for biological control and agricultural procedures, as well as on the planning of urban grass areas.

Kasvit muodostavat ensimmäisen ravintoketjun tason eli trofiatason maaekosysteemeissä, ja näin ollen toimivat ravinnon ja energianlähteinä ylemmille trofiatasoille. Kasvinsyöjät eli herbivorit, hedelmänsyöjät eli frugivorit ja symbionttiset endofyyttisienet ovat suoraan riippuvaisia kasveista, kun taas herbivoreja syövien petojen riippuvuus kasveista on epäsuoraa. Eri trofiatasoilla olevat lajit ovatkin jatkuvassa vuorovaikutuksessa keskenään, minkä vuoksi kahden lajin väliset vuorovaikutussuhteet voivat vaikuttaa myös muihin lajeihin. Väitöskirjassani olen tarkastellut usean trofiatason välisiä yhteyksiä kasvien ja niille haitallisten ja hyödyllisten eliöiden, eli antagonistien ja mutualistien, välillä. Esimerkkeinä antagonisteista käytin hyönteis- ja lintuherbivoreja, kun taas mutualisteina käytin hyönteissyöjälintuja, endofyyttisieniä ja siementenlevittäjälintuja. Tutkimuksissa I-II tutkin herbivorian aiheuttamien kasvista haihtuvien yhdisteiden, ja lehdissä tapahtuvien visuaalisten muutosten vaikutusta hyönteissyöjälintujen ravinnonhankintakäyttäytymiseen. Kasvit reagoivat sekä paikallisesti että kokonaisvaltaisesti herbivorian aiheuttamiin vaurioihin. En kuitenkaan löytänyt selvää tukea sille, että haihtuvat yhdisteet toimisivat hajuvihjeinä linnuille. Sen sijaan sain selville, että kasvinsyöjien aiheuttamat vauriot voivat vaikuttaa kasvin vahingoittumattomien lehtien ulkonäköön, joskin nämä muutokset voivat olla lintujen visuaalisen erotuskyvyn rajoilla. Herbivorian aiheuttamat muutokset kasvissa voivat lisäksi tehdä kryptisestä herbivorista vähemmän näkyvän linnuille, vaikka linnut todennäköisesti erottavatkin herbivorin lehtiä vasten riippumatta siitä onko kasvia vahingoitettu vai ei (II). Tutkimuksessa III tutkin voivatko endofyyttisienet suojella heiniä hanhien laidunnukselta. Tässä tutkimuksessa käytin kahta heinälajia, jotka eroat karkeudeltaan. Molemmilla lajeilla osa yksilöistä oli luontaisesti endofyytillisiä ja osa endofyytittömiä. Tulokseni osoittavat, että hanhet suosivat pehmeämpää ruoholajia karkean ruohon sijaan riippumatta endofyyttisienen läsnäolosta. Tutkimuksessa IV testasin aiheuttaako hyönteisherbivoria allokaatiokustannuksia kasville vaikuttamalla marjojen kypsymiseen tai biokemialliseen koostumukseen. Tutkin myös mahdollisia herbivorian aiheuttamia ekologisia kustannuksia kasville, joita mittasin marjojen todennäköisyytenä tulla siementenlevittäjien syömiksi. Tulokseni osoittavat, että marjoilla, jotka kasvoivat varvuissa lähellä herbivorien vaurioittamia varpuja, oli pienempi todennäköisyys tulla siementenlevittäjien syömiksi. Herbivoria ei vaikuttanut marjojen kypsymiseen tai biokemialliseen koostumukseen. Tämä viittaa siihen, että klonaalisilla kasveilla herbivoria voi aiheuttaa puolustusreaktion vahingoittumattomissa naapurikasveissa, mikä voi vaikuttaa myös kasvien mutualisteihin. Tämän väitöskirjan tutkimukset syventävät ymmärrystämme siitä, miten kasvit reagoivat herbivoriaan, ja miten nämä reaktiot vaikuttavat kasvien mutualisteihin. Tutkimukseni lisäävät myös tietoa herbivorien ja kasvien mutualistien ravinnonhankintakäyttäymisestä. Tällainen tieto on oleellista niin biologisen torjunnan kuin maataloudenkin kannalta, ja sitä voidaan soveltaa myös viheralueiden suunnittelussa.